Identifying important conservation areas for the clouded leopard Neofelis nebulosa in a mountainous landscape: Inference from spatial modeling techniques - Penjor, U; Macdonald, DW; Wangchuk, S; Tandin,; Tan, CKW (Wiley, 2018)
The survival of large carnivores is increasingly precarious due to extensive human development that causes the habitat loss and fragmentation. Habitat selection is in-fluenced by anthropogenic as well as environmental factors, and understanding these relationships is important for conservation management. We assessed the en-vironmental and anthropogenic variables that influence site use of clouded leopard Neofelis nebulosa in Bhutan, estimated their population density, and used the results to predict the species’ site use across Bhutan. We used a large camera-trap dataset from the national tiger survey to estimate for clouded leopards, for the first time in Bhutan, (1) population density using spatially explicit capture–recapture models and (2) site-use probability using occupancy models accounting for spatial autocorrela-tion. Population density was estimated at ̂DBayesian=0.40 (0.10 SD) and ̂Dmaximum−likelihood=0.30 (0.12 SE) per 100 km2. Clouded leopard site use was positively associated with forest cover and distance to river while negatively associated with elevation. Mean site-use probability (from the Bayesian spatial model) was ̂ψspatial=0.448 (0.076 SD). When spatial autocorrelation was ignored, the probability of site use was overestimated, ̂ψnonspatial=0.826 (0.066 SD). Predictive mapping al-lowed us to identify important conservation areas and priority habitats to sustain the future of these elusive, ambassador felids and associated guilds. Multiple sites in the south, many of them outside of protected areas, were identified as habitats suitable for this species, adding evidence to conservation planning for clouded leopards in continental South Asia.